O Grande Parque Residencial da Boavista, 1962-1973 - Inês Sofia Teixeira Sousa Alecrim (2014)
Housing, society, family, home, individual, these are the themes that motivates me the most in architecture. More than referenced and studied I prefer to consider each of them as a whole, in association with each other. To these motivations I add two others, these ones local and temporal, referring to the Modern Movement in Porto. Understand how this Movement translated itself in housing and society, which reflections it had in the new habits and ways of life, in the upper class and the lower class of Porto's society, and finally understand this path way in the 60´s, where the object of study, the Parque Residencial da Boavista by Agostinho Ricca, João Serôdio e José Carlos Magalhães Carneiro, stands - those are the main goals that my study aims. These goals start by analyzing the Parque Residencial da Boavista in the Portuguese context, in the way to understand if this project illustrates the continuity of the past and/or the present, or in the other hand if this is an isolated piece. Just after, we try to understand and detailing this urban complex by studying the different scales from the neighbourhood to the house, arriving to the new ways of living of this Modern society - here we will figure if this model of dwelling can be used and transposed to the social housing of this same period. At last, understand and conclude the relationship between the Modern Movement and the Modern housing in Porto through Parque Residencial da Boavista, giving us the answer of what it means a project like this in the Porto's panorama and what it means to his families and individuals in different classes of society.